The Tasmanian atrial fibrillation study: Transition to direct oral anticoagulants 2011-2015 - Alamneh, E.; Stafford, Leanne; Bereznicki, L. (Wiley-Blackwell Publishing Ltd., 2017)
© 2017 John Wiley & Sons Ltd Introduction: Contemporary Australian data regarding antithrombotic prescribing patterns following approval of direct oral anticoagulants (DOACs) in patients with atrial fibrillation (AF) are limited. Aim: The aim of this study was to assess antithrombotic prescribing patterns before, during, and after the clinical introduction of DOACs. Methods: Using digital medical records, this retrospective cohort study included all patients with AF as a primary or secondary diagnosis who were admitted to the Royal Hobart Hospital, Tasmania, Australia, between January 2011 and July 2015. Results: Antithrombotic agents were prescribed for 2078 (91.9%) of 2261 patients without documented contraindication to therapy. Higher rates of OAC prescribing were observed following government subsidization of DOACs in Quarter 3 (Q3) 2013 than anticoagulation rates in the prior quarters (54.4% in Q3, 2013, to 68.1% in Q2, 2015, P < .001), with the prescribing of warfarin and antiplatelet agents declining. DOACs, as a class, accounted for 18.4% of patients on antithrombotic therapy in 2011-2015; the proportion of patients receiving a DOAC steadily increased from 3.9% among OAC users in Q3, 2011, to 67.6% in Q2, 2015 (P < .001). In a subset of patients with newly diagnosed AF, patients commenced on DOACs were younger (70.4 vs 73.8 years, P=.04) and had lower stroke and bleeding risk scores (CHA2DS2-VASc 2.8 vs 3.3, P=.03, HAS-BLED 2 vs 3, P=.04) than patients who were newly prescribed warfarin. Conclusions: Direct oral anticoagulants rapidly became the most commonly prescribed class of antithrombotic medications in patients with AF soon after they became widely available. Warfarin and antiplatelet prescribing declined significantly, although a substantial proportion of patients continued to be prescribed antiplatelet therapy. Patients who were initiated on DOACs were typically younger with fewer comorbid conditions compared with those initiated on warfarin therapy.